Genetics of Parkinson´S Disease: Recessive Forms; [Genética en la Efermedad de Parkinson: Formas Recesivas] - Chana-Cuevas, P (Spanish Society of Neurology, 2024)
The genes associated with autosomal recessive Parkinson s disease (PD) include the PRKN, PINK1, and DJ-1 genes. Homozygous and compound heterozygous carriers of pathogenic variants of these genes tend to display typical characteristics of PD at early ages. On the other hand, the ATP13A2, FBXO7, PLA2G6, SYNJ1, and DNAJC6 genes are associated with early-onset recessive forms that frequently present with pyramidal signs, ataxia, and oculomotor alterations, with early appearance of levodopa-induced motor fluctuations and dyskinesia. Such non-motor symptoms as depression, psychiatric disorders, hallucinations, and epilepsy are also more frequent in this group. Among multiple molecular mechanisms involved in these cases, key examples are the dysfunction of mitochondrial and lysosomal processes. This article presents a brief review intended to inform clinicians about the basic molecular mechanisms and phenotype–genotype relationship of these monogenic forms of PD. © 2024